Study on behavior of partially prefabricated steel reinforced concrete stub columns under axial compression. (15th November 2019) - Yang, Yong; Chen, Yang; Feng, Shiqiang
Highlights: We conducted the test on axial behavior of PPSRC column. Several influences on the structural behavior of PPSRC column were explored. The formula for predicting the axial capacity of PPSRC column was proposed. Abstract: This paper aims to investigate the axial behavior and axial ultimate strength of partially prefabricated steel reinforced concrete (PPSRC) stub columns subjected to axial load. Eleven solid PPSRC column specimens and three hollow PPSRC column specimens were tested to examine the failure mode, the load-displacement response and the axial bearing strength of PPSRC columns. The effects of stirrup spacing, cast-in-place concrete strength and flange shear studs on the axial performance of PPSRC columns were also analyzed. Furthermore, an effective confinement stress from steel shape on the concrete was established on the basis of existing literature. The test results indicated that the PPSRC stub columns exhibited high axial load capacity and good deformability. Higher strength of inner concrete and smaller spacing of stirrups results in higher axial resistance, but the shear studs on the flange of steel shape were not effective on enhancing the axial-carrying capacity. Calculation formula to predict the compressive capacity of PPSRC columns was proposed based on the tested results. By comparison, it was found that the calculated results agreed well with the test results, which indicated that the proposed method had adequate accuracy and can be used in engineering application.